Sustainable utilization of red mud waste (bauxite residue) and slag for the production of geopolymer composites: A review. (June 2022) - Qaidi, Shaker M.A.; Tayeh, Bassam A.; Isleem, Haytham F.; de Azevedo, Afonso R.G.; Ahmed, Hemn Unis; Emad, Wael
Abstract: The production of cement results in the emission of much carbon dioxide, which contributes to ‎ ‎undesirable environmental impacts such as climate change and global warming. These ‎phenomena ‎have rekindled interest in utilizing a variety of industrial waste products to ‎produce geopolymer ‎‎(GP) composites and alkali-activated (AA) binders in order to reduce the ‎usage of ordinary ‎Portland cement in building construction. Waste red mud (RM), also known as bauxite residue, is one of these ‎hazardous radioactive ‎waste materials that is formed as a by-product of Bayer's aluminum ‎manufacturing process. This ‎paper conducts a systematic review of the literature on the use of ‎RM and slag in the production ‎of red mud-slag geopolymer (RM-SGP). An overview of the ‎economic and environmental ‎impacts, physical and chemical properties, production, ‎distribution, classification, and potential applications ‎of RM are presented. ‎Besides, recent advancements in the usage of RM and slag for geopolymer ‎production are ‎described in terms of physical, mechanical, durability, and microstructure ‎ properties. Moreover, this ‎study attempts to chart a route toward a realistic valorization that ‎reflects both real and perceived ‎concerns, such as radioactivity, leaching, and the life cycle ‎assessment of red mud geopolymer (RM-GP). The potential ‎use of RM-SGP production indicates the need for further studies into ‎the mixture proportion ‎and combination of these two raw ingredients with other cementitious materials ‎leading to new ‎energy-saving and affordable building products and processes. Also, it is ‎recommended that ‎research efforts be directed ‎toward economic, life cycle, and environmental ‎assessments.‎